Crystallization paths and microstructures in ternary oxide systems with stoichiometric compounds - Lutsyk, V.; Zelenaya, A. (Видавництво Львівської політехніки, 2012)
The problems of computer model simulation of CаO-SiO2-Al2O3 system are considered. The phases trajectories in fields of liquidus CaO, 3CaO×SiO2, 3CaO×Al2O3 are analyzed. The crystallization stages for given compositions are illustrated by the mass balance diagrams.
Keywords: computer model; CaO-SiO2-Al2O3 system; crystallization paths; mass balances